Increased autophagy contributes to impaired smooth muscle function in neurogenic lower urinary tract dysfunction. Issue 8 (24th May 2018) - Eberli, Daniel; Horst, Maya; Mortezavi, Ashkan; Andersson, Karl‐Erik; Gobet, Rita; Sulser, Tullio; Simon, Hans‐Uwe; Salemi, Souzan
Abstract : Aims: To explore whether autophagy plays a role in the remodeling of bladder smooth muscle cells (SMCs) in children with neurogenic lower urinary tract dysfunction (NLUTD), we investigated the effect of autophagy in NLUTD in the paediatric population. Methods: Bladder biopsies were taken from children with NLUTD and healthy donors as controls. Samples were labeled with the SMC markers calponin, smoothelin, and the autophagy proteins LC3, ATG5, and Beclin1. The contractile ability of bladder derived SMCs was investigated. Results: ATG5 gene and protein was upregulated in NLUTD muscle tissue compared to normal bladder. NLUTD muscle exhibited a punctated immunostaining pattern for LC3 in a subset of the SMCs, confirming the accumulation of autophagosomes. Pronounced elevation of ATG5 in the SMC in NLUTD tissue was associated with a downregulation of the key contractile proteins smoothelin and calponin. Pharmacological blocking of autophagy completely stopped the cells growth in normal bladder SMCs. Inhibition of autophagy in the NLUTD SMCs, with already elevated levels of ATG5, resulted in a reduction of ATG5 protein expression to the basal level found in normal controls. Conclusions: Our study suggests that autophagy is an important factor affecting the remodeling of SMCs and the alteration of functionality in bladder smooth muscle tissue in the NLUTD. Since autophagy can be influenced by oral medication, this finding might lead to novel strategies preventing the deterioration of NLUTD muscle.